Anti-Inflammatory Drugs and Immunosuppressants in Rheumatological and Musculoskeletal Diseases - Mustafa, Syed Hassan; Durrani, Talha; Adnan, Saqib; Khan, Rabnawaz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine drug compliance among patients with rheumatological and musculoskeletal diseases and to identify the reasons behind poor compliance.Study Design: Cross-sectional study.Place and Duration of Study: Department of Rheumatology Lady Reading Hospital, Peshawar Pakistan, from Aug 2020 to Feb 2021.Methodology: All patients aged 16 to 70, of either gender with inflammatory rheumatic diseases who were prescribed conventional DMARDs for at least six months were included in the study.Results: Two hundred and eighteen patients were included in the study. There were 59(27.1%) males and 159(72.9%) females with a mean age of 38.56±4.75years. There were 156 SPRA patients (71.5%), while SLE and SNIA accounted for 22(10.1%) and 17(7.8%) cases, respectively. Methotrexate was the most commonly prescribed medicine, 158(72.5%) while 90(41.3%) patients were prescribed Hydroxychloroquine and 43(19.7%) patients were prescribed Sulfasalazine. Regarding compliance, 112 (51.4%) patients were found to have good drug adherence. On the other hand, side effects and lack of awareness were found to be the most common cause of poor medication adherence.Conclusion: We concluded that adherence to medication among patients with inflammatory rheumatic and musculoskeletal diseases is poor